Activities of the 44th Japanese Antarctic Research Expedition (JARE-44) wintering party, 2003-2004 - Hideyasu Kojima (National Institute of Polar Research, 2005)
The 44th Japanese Antarctic Research Expedition (JARE-44) wintering party conducted the VIth five-year JARE program from February 1st 2003 to January 31st 2004 at both Syowa and Dome Fuji Stations. Thirty-six members at Syowa Station and 8 members at Dome Fuji Station were engaged in the various scientific and logistic activities. Many observation programs in meteorology, upper atmospheric physics, atmospheric sciences and glaciology, geophysics and biology and medical science were carried out in addition to logistic activities such at Syowa Station. As sea ice in Ongul Strait was unstable until early August, the start of the field activities in the southern coastal area was delayed until early October. However, many field teams engaged in seismic, Global Positioning System (GPS) observations and a penguin census study made observations around the coastal area of east Lutzow-Holm Bay in October and November when sea ice was stable.